Gas liquid chromatography for detection of bacteriuria: examination for volatile acidic and neutral compounds. Issue 9 (September 1978) - Barrett, E; Lynam, G; Trustey, S
Abstract : Direct injection of clinically infected urines on porous-polymer columns was investigated to determine which microbial metabolites were consistently detectable, and whether their presence could be used as a reliable index of infection. Chromosorb 101 was found to be the most suitable porous polymer for the detection of microbial metabolites; greater sensitivity of detection was achieved by partial purification of the urine before injection. Acetic acid was the only compound found consistently and it enabled 10(6) microorganisms per ml to be detected in urine. However, as urinary tract infection is diagnosed by the presence of 10(5) organisms or more per ml, our method is insufficiently sensitive for the detection of bacteriuria. Escherichia coli, Enterobacter cloacae, Klebsiella spp, Proteus spp, Stapyhlococcus albus, and Streptocococcus faecalis were detectable by our method but Pseudomonas aeruginosa and Candida albicans were not.